(untitled) (Research, Society and Development, 2025)
The purpose of this study is to highlight the main risk factors associated with the development of bacterial vaginosis in women, through a literature review. carried out from articles selected from the SCIELO, BVS and PUBMED databases. The inclusion criteria were: articles on the subject, published between 2020 and 2025. With rgard to exclusion criteria:criteria were defined : articles related to the theme, published between 2020 and 2025. Regarding the Exclusion Criteria: Works that dipapers that did not correspond to the theme and prior to 2020 were excluded. 20 papers aligned with the proposed theme were included. From the results obtained, it can be seen that the risk factors associated with bacterial vaginosis include: use of an IUD, smoking, vaginal douches, vaginal sex with multiple partners, clothing. This condition can increase the risk of more serious complications, such as PID, susceptibility to acquiring Sexually Transmitted Infections (STIs) and an increased risk of premature birth. These complications can damage psychological and self-esteem, directly influencing quality of life and interpersonal relationships. In conclusion, it is essential to deepen knowledge about this condition, promoting guidelines aimed at prevention, based on the risk factors identified, and ensuring access to appropriate and effective treatments, these measures are essential to prevent the incidence of infection and improve women’s quality of life.